An Effective Algorithm for Economic Dispatch of Power System with Prohibited Operating Zone. Issue 1 (December 2020) - Wang, Shibo; WeiTeng,; Wang, Nan; Cheng, Yan; Sun, Shumin; Xing, Jiawei; Wang, Yanzhuo
Abstract: In the actual operation of the power system, some generating units may have physical limitations. For a unit with prohibited operating zone, its operation zone [Pmin, Pmax] will be divided into several discrete sub feasible regions. In this paper, the influence of units with prohibited operating zone on the system is deeply studied, and the influence of units with prohibited operating zone on other units in the system, including the influence between units with prohibited operating zone, and the optimal solution state of economic dispatch problem for units with prohibited operating zone are further studied. Then the iterative algorithm for the above three problems is modified. At the same time, the economic law and physical essence of the economic dispatch problem for units with prohibited operating zone are explored. With high calculation efficiency, the algorithm proposed in this paper has its own engineering application value.